Sub-National Government and the Problem of Unequal Development in ASEAN Economic Integration: Case of Indonesia - Agus Suman; Pantri Muthriana Erza Killian; Ni Komang Desy Arya Pinatih (JAS (Journal of ASEAN Studies), 2017)
Economic integration, as a prevalent phenomenon in contemporary international relations, brings with it several problems including in the practice of development. Krapohl & Fink (2013) argue that regional integration can follow three different developmental paths which are intra-regional interdependence, extra-regional dependence and intra-regional asymmetries and hence regional integration can actually reinforce current situations rather than changing it. With regards to this, ASEAN is following the second path, creating a reliance on external actors and thus requiring member states to be highly competitive in the global level. However, this strategy ignores an important element, the intra-national development gap, since ASEAN is mostly focused in overcoming the intra-regional gap. This paper therefore seeks to elaborate the problem of increasing intra-national development gap due to regional integration by using Indonesia as a case study. The findings show that regional integration in Indonesia can actually widen the national development gap due to three main reasons. First, ASEAN integration is highly top-down in nature, thus limiting the role of Indonesia’s sub-national governments (SNGs) and private actors in the process; second, differing capacity of Indonesia’s sub-national governments to engage in IR provides higher opportunities for some while creating hindrances for others and lastly, the high transactional cost of intra-national economic activities in Indonesia causes the benefits of economic integration to be highly concentrated in one area. Therefore, there needs to be a larger role for SNGs in regional integration particularly in the most underpriviliged area of Indonesia.